Analisis Integrasi Ranah Afektif, Kognitif, dan Psikomotorik dalam Pembelajaran Bahasa Arab di Madrasah Aliyah: Perspektif Kurikulum Merdeka - Elyatul Mu'awanah; Ita Nurmala (Yayasan Al-Afif, 2024)
This study aims to analyze the integration of affective, cognitive, and psychomotor domains in Arabic language learning at Madrasah Aliyah (MA) 1 Annuqayah Putri from the perspective of Merdeka Curriculum. The method used is document analysis, which involves collecting and evaluating official curriculum documents, teaching materials, and teaching guides implemented at the school. The data were analyzed based on criteria that identified the essential elements of each domain: the cognitive domain which focuses on knowledge and understanding, the affective domain which deals with attitudes and motivation, and the psychomotor domain which includes practical skills. The results of the analysis show that in MA 1 Annuqayah Putri there are significant efforts to integrate the three domains, but there are still challenges in emphasizing the affective and psychomotor aspects. This research provides recommendations for the development of more comprehensive learning materials and strategies, in order to increase the effectiveness of Arabic language learning in schools. Thus, it is hoped that this research can be a reference for curriculum development that is more effective and responsive to the needs of students at MA 1 Annuqayah Putri.